2012
DOI: 10.2106/jbjs.j.01033
|View full text |Cite
|
Sign up to set email alerts
|

Conflict of Interest in the Assessment of Thromboprophylaxis After Total Joint Arthroplasty

Abstract: Most studies on thromboprophylaxis after total joint arthroplasty are sponsored by industry. Moreover, the qualitative conclusions in those studies are favorable to the use of the sponsored prophylactic agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
3

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 74 publications
0
8
0
3
Order By: Relevance
“…Surgeons with listed conflict of interest give testimonials to the benefit of liposomal bupivacaine without providing data to support opinion [28]. Previous investigations on potential conflict of interest in orthopedic research have demonstrated that positive studies are much more likely to be published than negative studies when potential conflicts of interest exist [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Surgeons with listed conflict of interest give testimonials to the benefit of liposomal bupivacaine without providing data to support opinion [28]. Previous investigations on potential conflict of interest in orthopedic research have demonstrated that positive studies are much more likely to be published than negative studies when potential conflicts of interest exist [29,30].…”
Section: Discussionmentioning
confidence: 99%
“…Such data might save billions of dollars for our national health systems and prevent patients from being treated for an unnecessarily long time. However, the industry that has supported the current trials (Eriksson et al 2008, Kakkar et al 2008, Turpie et al 2009, Lassen et al 2010a, b, Lee et al 2012) will probably neither sponsor nor initiate such studies, for obvious reasons.…”
mentioning
confidence: 99%
“…From 2004 to 2010, sixty-six studies published in PubMed-cited literature with identified industry or nonindustry funding were reviewed to determine whether a treatment was classified as favorable, neutral, or unfavorable in the prevention of clotting. Only two of the fifty-two industry-sponsored studies had negative results, in contrast to negative findings being observed in three of the fourteen studies without industry support 15 . A study of articles published in the MEDLINE database between 1980 and 2002 revealed a significant relationship between industry sponsorship and pro-industry conclusions 16 .…”
Section: Ensuring Accuracy In Researchmentioning
confidence: 70%
“…In a recent study in The Journal of Bone & Joint Surgery, a significant association was found between the funding source and the qualitative conclusions in publications examining the prevention of deep vein thrombosis following total joint arthroplasty 15 . From 2004 to 2010, sixty-six studies published in PubMed-cited literature with identified industry or nonindustry funding were reviewed to determine whether a treatment was classified as favorable, neutral, or unfavorable in the prevention of clotting.…”
Section: Ensuring Accuracy In Researchmentioning
confidence: 99%